2014
DOI: 10.1002/chem.201403293
|View full text |Cite
|
Sign up to set email alerts
|

Gold(I)‐Catalysed Direct Thioetherifications Using Allylic Alcohols: an Experimental and Computational Study

Abstract: A gold(I)-catalysed direct thioetherification reaction between allylic alcohols and thiols is presented. The reaction is generally highly regioselective (SN2′). This dehydrative allylation procedure is very mild and atom economical, producing only water as the by-product and avoiding any unnecessary waste/steps associated with installing a leaving or activating group on the substrate. Computational studies are presented to gain insight into the mechanism of the reaction. Calculations indicate that the regiosel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 97 publications
0
20
0
Order By: Relevance
“… 6b , c , 17 Indeed, during our related studies using thiols for thioetherification reactions, chirality transfer does not occur in the thioetherification reactions. 7a , 18 Experimental and computational studies showed that the racemisation is due to isomerisation between the formal S N 2′ and S N 2 thioether products. Clearly, using alcohol instead of thiol as a nucleophile allows for successful chirality transfer, except in certain substrates, such as β-substituted 4 m and 4 n (entries 12–13, Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 6b , c , 17 Indeed, during our related studies using thiols for thioetherification reactions, chirality transfer does not occur in the thioetherification reactions. 7a , 18 Experimental and computational studies showed that the racemisation is due to isomerisation between the formal S N 2′ and S N 2 thioether products. Clearly, using alcohol instead of thiol as a nucleophile allows for successful chirality transfer, except in certain substrates, such as β-substituted 4 m and 4 n (entries 12–13, Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…One of the key research efforts within our group has been to develop gold-catalysed 5 regioselective methods towards allylic ethers 6 and allylic thioethers. 7 Within this context, we recently developed a mild and air-stable gold(I)-catalysed direct allylic etherification of allylic alcohols. 8 This dehydrative formal S N 2′ procedure 9 requires neither the allylic alcohol electrophile nor the alcohol nucleophile to be activated (either to install a leaving group in the former or form an alkoxide in the latter), leading to mild reaction conditions that are tolerant of various functional groups as well as air and moisture (Scheme 1 a).…”
Section: Introductionmentioning
confidence: 99%
“…Our interest in this area arose from our previousw ork on gold catalysis; [11] in particular, the mild gold-catalysed [12] protoand deuterodeboronations [13] and cross-couplings (Scheme 1A(a) and (b), respectively). [14] We hypothesisedt hat the organogold intermediate I [15] should reactw ith NIS to rapidly form iodoarenes 3.T herefore,o ur aims were to 1) compare the gold-catalysed andu ncatalysed reactions to ascertain whether gold catalysis can be used to overcome some of the substrate scopel imitations of the uncatalysed reaction, 2) develop a much faster iodination protocol, both catalysed and uncatalysed,3 )utilise environmentally friendly solvents to significantly improvet he practicality of the reaction( the original reaction times were 1.5-25 hi na cetonitrile), [6] and 4) to apply the methodology to radioiododeboronations.…”
Section: Introductionmentioning
confidence: 99%
“…Lee and co-workers (2014) documented the synthesis of allylic thioethers 46,b y condensing p-alcohols (7)w ith unactivatedt hiols in the presence of [JohnPhosAu(ACN)]SbF 6 (Scheme 12). [35] Higher yields (up to 92 %) were accessible by portion-wisea ddition of the gold catalystt ot he solution. Moreover,a lthought hiophenols (45 a)p erformed well at 35 8C( 24 h), more basic aliphatic thiols (45 b)r equired harshr eaction conditions (72 h, 45-60 8C).…”
Section: Cànb Ond-forming Processesmentioning
confidence: 99%
“…As a consequence, the gold‐catalyzed thioether formation has been far less investigated. Lee and co‐workers (2014) documented the synthesis of allylic thioethers 46 , by condensing π‐alcohols ( 7 ) with unactivated thiols in the presence of [JohnPhosAu(ACN)]SbF 6 (Scheme ) . Higher yields (up to 92 %) were accessible by portion‐wise addition of the gold catalyst to the solution.…”
Section: Allylic Substitutionsmentioning
confidence: 99%